The Invention of the Brain: Artificial Intelligence and Libidinal Symptomatology - Lee, Alex Taek-Gwang (Archīum Ateneo, 2024)
In this essay, I discuss how the mechanical scan of the brain becomes to be identified with consciousness. For this purpose, I examine Angelo Mosso’s ergograph and its influence on modern psychology. The fundamental problem of his experiment lies in that nobody knows how he measured the blood flow in the brain. Mosso’s method to investigate the brain was unknown, but his description of the neural mechanism spread widely. However, Mosso’s basic assumption has not fundamentally changed, even in today’s neuroscientific context. The technological evolution offers more detailed images of the brain, but it does not necessarily allow us to understand the effects of its mechanism far differently from Mosso’s early description. The visual images of the brain do not explain the mind-body relation adequately. William James’s and Gilles Deleuze’s insight into the said experiment disclose the vantage point of neuroscience. My conclusion is that the effects of the brain cannot be reduced to the scanned images of its mechanism.